Does Religion Bias Individuals Against Female Political Leadership in Latin America?. Issue 4 (9th December 2015) - Setzler, Mark
Abstract : This study explores the relationship between several dimensions of religiosity and biases against female political leadership within 15 Latin America countries. The central finding is that religious characteristics are correlated with pro‐male bias in many countries; however, the relationship varies in strength and even direction from one country to the next. Analyses of a subset of religiously diverse nations further demonstrate that individual‐level gender biases against female leadership have no systematic connection to country‐level differences in secularization or levels religious pluralism.